Odpowiedź :
Odpowiedź:
2(x-5)=3(x+7)
2x-10=3x+21
-x=31
x=-31
10+5(x+6)=2x-(3-x)
10+5x+30=2x-3+x
43=-2x
x=-21,5
-4(2x-6)-4x=5+5(x+8)
-8x+25-4x=5+5x+40
-12x+24=45+5x
-17x=21
x=-17/21 = -1 4/17
[tex]1)\\\\2(x-5)=3(x+7)\\\\ 2 x-10=3 x+21\\\\2x-3x=21+10\\\\-x=31\ \ |*(-1)\\\\x=-31[/tex]
[tex]2)\\\\ 10+5(x+6)=2x-(3-x)\\\\10+5 x+30=2x- 3+x\\\\5x+40=3x-3\\\\5x-3x=-3-40\\\\2x=-43\ \ |: 2\\\\x=-\frac{43}{2}=21,5[/tex]
[tex]3)\\\\ -4(2x-6)-4x=5+5(x+8)\\\\-8x+24-4x=5+5 x+40\\\\-12x+24=5x+50\\\\-12x-5x=45-24\\\\-17x=21\ \ |:( -17)\\\\ x=-\frac {21}{17} =-1\frac{4}{17}[/tex]